2018
DOI: 10.5430/afr.v7n3p172
|View full text |Cite
|
Sign up to set email alerts
|

Analyst Coverage and Earnings Management Using Classification Shifting

Abstract: This study examines the association between analyst coverage and classification shifting. Prior studies on external monitoring factors and classification shifting provide mixed results: international studies (Haw, Ho, & Li, 2011;Behn, Gotti, Herrmann, & Kang, 2013) find that external monitoring factors mitigate classification shifting, while Abernathy, Beyer, and Rapley (2014) find that external monitoring factors promote classification shifting when accrual-based earnings management and real earnings manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Foreign ownership acts as a monitoring mechanism that aims to ascertain whether the manager (agent) has acted in accordance with the company's objectives. The audit process is one of the corporate governance mechanisms that provide guarantees for stakeholders in the financial reporting process [20]. The function of the auditor is to ensure that the financial information presented meets accounting standards.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Foreign ownership acts as a monitoring mechanism that aims to ascertain whether the manager (agent) has acted in accordance with the company's objectives. The audit process is one of the corporate governance mechanisms that provide guarantees for stakeholders in the financial reporting process [20]. The function of the auditor is to ensure that the financial information presented meets accounting standards.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…On the other hand, Francis and Wang (2008) conclude that there is no systematic difference in terms of earnings quality between the companies audited by the big four auditors and the companies audited by non-big fours in the countries where investor protection is weak. Zhao (2012) examined how different external control and monitoring mechanisms relate to use of classification shifting to manage earnings. As a result of the empirical evidence provided in the study, Zhao (2012) concluded that the companies are more likely to use classification shifting in earnings management, depending on the increase in the level of external audit or the quality of external audit.…”
Section: Development Of Hypothesismentioning
confidence: 99%
“…Zhao (2012) examined how different external control and monitoring mechanisms relate to use of classification shifting to manage earnings. As a result of the empirical evidence provided in the study, Zhao (2012) concluded that the companies are more likely to use classification shifting in earnings management, depending on the increase in the level of external audit or the quality of external audit. Barua and Zhao (2014) find that audit quality measured by big four auditors and industry expertise of auditors was more related to classification shifting.…”
Section: Development Of Hypothesismentioning
confidence: 99%